2020
DOI: 10.1155/2020/3242854
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Volatile Compounds during the Fermentation Process of Yogurts by Streptococcus thermophilus Based on Odor Activity Value and Heat Map Analysis

Abstract: The volatile composition of yogurt produced by Streptococcus thermophilus fermentation at different time points was investigated by gas chromatography-mass spectrometry combined with simultaneous distillation and extraction. A total of 53 volatile compounds including 11 aldehydes, 10 ketones, 8 acids, 7 benzene derivatives, 13 hydrocarbons, and 4 other compounds were identified in all of the samples. Ketones and hydrocarbons were the predominant volatile components in the early stage, whereas acids were the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 37 publications
0
15
1
Order By: Relevance
“…The clustering analysis and the corresponding heat maps are the most widely used of all bioinformatics, covering areas as diverse as genetics, medicine, geography and, more recently, food chemistry [ 63 , 64 ]. This graphical representation has been successfully used to assess moderately large data matrices because it is visually stimulating and easily interpreted [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…The clustering analysis and the corresponding heat maps are the most widely used of all bioinformatics, covering areas as diverse as genetics, medicine, geography and, more recently, food chemistry [ 63 , 64 ]. This graphical representation has been successfully used to assess moderately large data matrices because it is visually stimulating and easily interpreted [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ketones are a major class of volatile compounds identified in yogurt. They are derived both from raw milk (and as such, dessert yogurts from cow milk are expected to differ from those from goat milk in their ketone content) and from the processing parameters of yogurt production, due to the β-oxidation metabolic pathway of unsaturated fatty acids [ 15 , 26 ]. Dessert yogurts made from cow milk, prepared with the mild culture, without the addition of Bifidobacterium BB-12, had had a ketones content of around three times lower than the corresponding dessert yogurts prepared with the classic and acidic cultures (52.52 ± 12.98 mg kg −1 for the mild, 160.90 ± 52.47 mg kg −1 for the classic and 147.60 ± 50.54 mg kg −1 for the acidic culture), probably due to the specific action of the mild culture.…”
Section: Resultsmentioning
confidence: 99%
“…As aroma is critical for the acceptance of a food, it plays an important role in its commercialization. For this purpose, various studies have been carried out in order to identify the volatile compounds of foods including yogurt [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Of course, a number of volatile compounds are not always perceived as characteristic odors, as the compound contributing to a particular odor should be at a concentration greater than a minimum threshold [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 56 volatile compounds were detected by SPME-GC-MS in both inoculated milk samples, which exceeded the findings of FAAs in other yoghurt studies reported in the literature. With the use of Streptococcus thermophilus as a single starter strain in yoghurt fermentation, 53 volatile compounds have been reported [ 64 ], where 31 volatile compounds were attributed to the use of cow milk [ 65 ]. The 56 volatile compounds detected in this study were sub-classified into chemical groups as shown in Table 2 , as 10 carboxylic acids, 8 aldehydes, 11 ketones, 17 alcohols and 10 esters.…”
Section: Resultsmentioning
confidence: 99%